(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Gothic tourism is a new type of tourism and a new concept that has recently been in the discipline of English literature, and it is a distinct form of tourism of special interest that focuses on knowledge of Gothic beauty. This study aims to examine and criticize the concept of Gothic tourism and verify its use in some of the selected texts in Christopher Marlowe’s play "Dr. Faustus" This study tries to answer the following questions: 1-Is there Gothic tourism in Dr. Faustus play? 2-Does Gothic tourism reflect more positive or negative effects? 1-Finding out a new type of tourism of special interest in Christopher Marlowe’s play "Dr. Faustus". 2-Searching on the subject of this tourism because it is little bit exiting and determining the extent of its impact. It is hypothesized that gothic tourism is conceived as a particular form of tourism and can be considered a form of literary tourism. It offers as a link between dark and literary tourism.